2008
DOI: 10.5483/bmbrep.2008.41.1.055
|View full text |Cite
|
Sign up to set email alerts
|

Obestatin is present in saliva: alterations in obestatin and ghrelin levels of saliva and serum in ischemic heart disease

Abstract: Ghrelin and obestatin are a single gene products and are a multiple functional peptides that regulates energy homeostasis, and food intake. In the present work, we studied the secretion of ghrelin and its co-secreted peptide obestatin in 44 patients with ischemic heart disease with that of 27 healthy matched controls. Here we first conducted using an immunohistochemistry assay to screen whether human salivary glands have any obestatin immunoreactivity. Then, serum and saliva obestatin and acylated ghrelin leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
31
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 31 publications
1
31
0
2
Order By: Relevance
“…Reducing the expression of endothelial adhesion molecules like VCAM-1 confers an anti-atherogenic role to obestatin, while an increase in Ox-LDL uptake by macrophages leads to lipid accumulation and foam cell formation and eventually into fatty streak formation in the arterial wall leading to proatherogenic properties. Ozbay et al [42] demonstrated slightly higher concentrations of saliva ghrelin and obestatin in subjects with ischemic heart disease compared with control groups, suggesting that the two peptides can participate directly in the regulation of energy metabolism in ischemic heart tissue. Obestatin may also have a potential role in the regulation of blood pressure, as demonstrated by Ren et al [43] who found that there is a positive correlation between plasma obestatin concentration and mean arterial pressure in normal pregnant women and pregnant women with pregnancy-induced hypertension.…”
Section: Pathological Involvement Of Obestatinmentioning
confidence: 99%
“…Reducing the expression of endothelial adhesion molecules like VCAM-1 confers an anti-atherogenic role to obestatin, while an increase in Ox-LDL uptake by macrophages leads to lipid accumulation and foam cell formation and eventually into fatty streak formation in the arterial wall leading to proatherogenic properties. Ozbay et al [42] demonstrated slightly higher concentrations of saliva ghrelin and obestatin in subjects with ischemic heart disease compared with control groups, suggesting that the two peptides can participate directly in the regulation of energy metabolism in ischemic heart tissue. Obestatin may also have a potential role in the regulation of blood pressure, as demonstrated by Ren et al [43] who found that there is a positive correlation between plasma obestatin concentration and mean arterial pressure in normal pregnant women and pregnant women with pregnancy-induced hypertension.…”
Section: Pathological Involvement Of Obestatinmentioning
confidence: 99%
“…On the other hand, the number of trials investigating the correlation between acute pancreatitis and obestatin, the product of the same gene with ghrelin, is limited. Yet, obestatin is synthesized in a co-localized fashion with ghrelin in all organs producing ghrelin, and studies indicate that it has the reverse activity of ghrelin, regarded as anorexigenic, although a consensus has not yet been established regarding this standpoint (10). Therefore, this trial was designed to determine the role of the orexigenic "ghrelin" and anorexigenic "obestatin" hormones, if any, on the diagnosis and assessment of the severity of AP, in addition to conventional methods.…”
Section: Introductionmentioning
confidence: 99%
“…Salivary diagnostics also plays an important role in cardiology, i.e. in risk assessment for cardiovascular diseases in people with insulin resistance 111,112 or for acute miocardial infarction. 113 Thus, salivary alpha-amylase was reported as an independent diagnostic factor for acute myocardial infarction in patients suffering from precordial pain less than 4 h. 114 In addition, the use of nano-biochips based on salivary proteins (including C-reactive protein, myoglobin and myeloperoxidase) in patients with acute myocardial infarction was reported to be an effective technique for screening purposes.…”
mentioning
confidence: 99%